Seismic retrofitting of RC buildings using CFRP and post-tensioned metal straps: shake table tests - Garcia, Reyes; Pilakoutas, Kypros; Hajirasouliha, Iman; Guadagnini, Maurizio; Kyriakides, Nicholas; Ciupala, Mihaela Anca (My University, 2017)
This article examines the effectiveness of two innovative retrofitting solutions at enhancing the seismic behaviour of a substandard reinforced concrete building tested on a shake table as part of the Pan-European funded project BANDIT. To simulate typical substandard construction, the reinforcement of columns and beam-column joints of the full-scale structure had inadequate detailing. An initial series of shake table tests were carried out to assess the seismic behaviour of the bare building and the effectiveness of a first retrofitting intervention using Post-Tensioned Metal Straps. After these tests, columns and joints were repaired and subsequently retrofitted using a retrofitting solution consisting of Carbon Fibre Reinforced Polymers and Post-Tensioned Metal Straps applied on opposite frames of the building. The building was then subjected to unidirectional and three-dimensional incremental seismic excitations to assess the effectiveness of the two retrofitting solutions at improving the global and local building performance. The article provides details of the above shake table testing programme and retrofitting solutions, and discusses the test results in terms of the observed damage, global damage indexes, performance levels and local strains. It is shown that whilst the original bare building was significantly damaged at a peak ground acceleration (PGA) of 0.15 g, the retrofitted building resisted severe three-dimensional shake table tests up to PGA = 0.60 g without failure. Moreover, the retrofitting intervention enhanced the interstorey drift ratio capacity of the 1st and 2nd floors by 160 and 110 %, respectively. Therefore, the proposed dual retrofitting system is proven to be very effective for improving the seismic performance of substandard buildings.
Keywords: CFRP composites; Full-scale buildings; Post tensioned metal straps; Seismic retrofitting; Shake table tests; Substandard RC buildings